A proposed improvement of solid waste management for the Cavite City Public market - Apostol, Alex A.
The study focused on the assessment of the solid waste management practices and development of solid waste management plan for Cavite City public market. The study began with a review of the existing national laws and local ordinances related to solid waste management. Likewise, the profile of the city was presented to provide awareness and understanding of the existing conditions and clear insight of the existing practices and programs in solid waste management in the public market. Site inspection and short interview with the local officials concerned on solid waste management in the public market were undertaken simultaneously with secondary data gathering. Records from the Cavite City GSO showed that the public market is currently generating an average of 18.6 m3/d of solid waste, which represent about 10 percent of the total solid waste generated by the city. Observations within the study area revealed that no waste segregation or recycling is being undertaken in the Cavite City public market. Perception survey was conducted to obtain inputs from the stallholders and vendors who are the main waste generators in the public market. A total of 125 respondents representing 18 percent of the total stallholders participated in the perception survey. The survey showed that most of the respondents (90 percent) were satisfied with the current solid waste collection but the level of awareness of the respondents on solid waste management practices is below 50 percent. Recommendations obtained from the respondents to improve the public market solid waste management include: garbage should be placed in plastic bag (62 percent), dispose garbage in proper way (36 percent) and stallholders should learn waste segregation (11 percent). Waste Amount and Composition Surveys (WACS) were undertaken for seven consecutive days. It was found out that Cavite City public market is generating an average of 7.4 kg/stall/day of solid waste. The market solid waste, having a bulk density of 353kg/m3, consisted of fruits and vegetables (56 percent), animal parts (7 percent), coconut shell (5 percent), paper (8 percent), plastics (13 percent), wood (1 percent), clothing/textile (1 percent), glass (1 percent), metals/cans (1 percent) and other wastes (7 percent). Results of the interview with WACS were used to develop solid waste management plan for the combined old and new public market in Cavite City. The plan focused mainly on waste reduction at the source, waste segregation and processing at the Materials Recovery Facility (MRF). The daily waste generation from the combined 1,404 stalls of the new and old public market was projected at 10,400 kg or 30 m3. The proposed plan targeted to reduce 10 percent of total waste generation through reuse and recycling at the source. Waste segregation was also made mandatory. Further processing of collected wastes shall be done in MRF - compostable waste shall undergo composting while recyclable wastes shall be sold to junk shops and recycling industries and the remaining solid wastes shall be brought and disposed in the landfill. The proposed plan incorporates an intensive public education on waste reduction at the source and mandatory waste segregation. Public and private participation shall also be encouraged in the collection and use of compost materials in agricultural farm.